Hyperemia in head injury: can transcranial doppler help to personalize therapies for intracranial hypertension? - Gelormini, Camilla; Ioannoni, Eleonora; Scavone, Angela; Pisapia, Luca; Signorelli, Francesco; Montano, Nicola; Piastra, Marco; Caricato, Anselmo (Frontiers in Neurology, 2023)
Introduction An increase in cerebral blood flow is frequent after traumatic brain injury (TBI) and can lead to brain swelling and refractory intracranial hypertension. We hypothesized that Transcranial EcoDoppler (TCD) monitoring could be useful to detect the cause of intracranial hypertension in these patients. Our main objective was to investigate if the increase of velocity in the middle cerebral artery (MCA) on TCD could be associated with intracranial hypertension. Methods We retrospectively studied TBI patients consecutively monitored with TCD. Hyperemia was defined as MCA mean velocity higher than 80 cm/s. Intracranial hypertension was considered when hyperosmolar therapy, hyperventilation, or deep sedation was used. Results We found hyperemia in 40 patients out of 118 (33.9%). On average, it started at day 2.1 ± 0.9 from admission and significantly increased (MCA velocity at day 1: 74 ± 25 cm/s vs. 109 ± 36 cm/s at day 4; p < 0.001). Intracranial hypertension was significantly associated with hyperemia, occurring in 92.5% of hyperemic and 51.3% of non-hyperemic patients (p < 0.001). Moreover, we found that hyperemia preceded severe intracranial hypertension (p < 0.0001). In a logistic regression model, hyperemia was the only variable significantly correlated with intracranial hypertension (OR 10.64; p < 0.001). Discussion Hyperemia was frequent in our population of TBI patients and preceded intracranial hypertension. TCD monitoring, if performed on a daily regular basis, can be a useful method to detect this phenomenon and to guide the therapy. It could be a tool for a cause-oriented therapy of intracranial hypertension.